ANALYSIS OF THE PHILOSOPHY OF FACILITIES AND INFRASTRUCTURE MANAGEMENT IN IMPROVING THE PERFORMANCE OF EDUCATORS AND EDUCATIONAL STAFF AT MTSN 1 PASER - Riduan; Muhammad Saparuddin (PT. Berkah Smart Academica, 2024)
This study aims to investigate the management of educational facilities and infrastructure in enhancing the performance of educators and educational staff at MTsN 1 Paser. The research object consists of planning, determination, inventory, maintenance, and disposal. This is a qualitative descriptive study, with four teachers as the research subjects. Data was collected through three methods: interviews, observations, and documentation. The research findings indicate that the planning of facilities and infrastructure in the learning process involves needs analysis (school self-evaluation), financing, and priority analysis. The provision of facilities and infrastructure in the learning process is sourced from repairs, government funds, community contributions, borrowed items, and considerations of quality and functionality in the learning process. Additionally, the inventory of facilities and infrastructure is conducted during activities. The results of the study demonstrate that the implementation of the philosophy of facilities and infrastructure management at MTsN 1 Paser has a positive impact on the performance of educators and educational staff. Recommendations include optimizing planning, inventorying, and repairing damaged equipment.